Parathyroid carcinoma: case report - Silva, Matheus Henrique de Freitas; Morais, Pedro Otávio de Resende; Souza, Thaís Andrade de; Muniz, André Luis Ribeiro; Silva, Bárbara C; Noviello, Thiago Bechara; Andrade, Marcella Menezes (Medicina (Ribeirao Preto), 2018)
Parathyroid carcinoma (PC) is an uncommon pathology which has propaedeutic and therapeutic peculiarities. In general, it presents as symptomatic primary hyperparathyroidism, that corresponds to only 1% in this subgroup. Both the clinical and histological diagnosis of PC are difficult due to inconsistent criteria. Laboratorial exams commonly present hypercalcemia and PTH well-above the reference value. Surgery is the only curative and effective treatment for parathyroid carcinoma. Case report: Patient M.P.R.L., 48 years old, female, melanodermic, native and from Felisburgo - MG. The disease had been progressing for 2 years with progressive weakness, anemia, renal dysfunction, chronic pain and weight loss (about 15 kg in last five months), associated with PTH-dependent hypercalcemia and renal function decline. A cervical study showed the presence of two thyroid nodules whereas a parathyroid scintigraphy showed no evidence of glands hyperplasia or adenoma. She was admitted to the Santa Casa Hospital of Belo Horizonte for a propaedeutic and therapeutic management of the presented profile.